Perancangan Sistem Informasi Keuangan Berbasis Web Pada Toko Sumber Hidayah - Rizqi Hidayah; Kiky Zulkifli (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to assist Toko Sumber Hidayah in managing transactions through a web-based information system. Previously, the store relied on manual bookkeeping, which often caused calculation errors, data loss, reporting delays, and difficulties for the owner in monitoring financial conditions in real time. This research uses the System Development Life Cycle (SDLC) method with a waterfall model approach. The stages include observation, needs analysis, system design using UML, implementation using PHP and CodeIgniter, testing with Blackbox Testing, and system deployment. Data collection was carried out through direct observation at Toko Sumber Hidayah, interviews with the store owner, and literature review. The results show that the developed system improves the accuracy of financial recording, simplifies inventory monitoring, accelerates the preparation of income statements, and assists in controlling customer receivables. Blackbox Testing results indicate that all features function as expected.